"Just treat me as a teacher!" Mapping language teacher agency through gender, race, and professional discourses. (December 2018) - Vitanova, Gergana
Abstract: Drawing on a longitudinal project, this paper focuses on the micro-aspects of emergent agency in several English-as-a-second-language teachers in training with a focus on the causative social factors that mediate this construct. Specifically, as it employs multimedia narrative structures, including written texts, images, and interviews, it traces how gender, race, and culture mediate the formation of their agentive selves. These factors are not isolated from one another but interact closely. Findings reveal how the participants respond to the often stereotypical discourses of gender and race in their personal and professional relationships with others. They show that by employing multimodal spaces for unique personal, on the one hand, and larger, social positionings, on the other, the narratives provide the teachers with the opportunity for active awareness, resistance, and transformative practices. The paper and the analysis are informed by ecological perspectives on agency and Bakhtin's views of relational selves and social responsibility.